ARE INSURANCE & WEALTH MANAGEMENT INCOME AND ADVISORY SERVICE INCOME BETTER BOLSTERS TO COMMERCIAL BANKS’ PERFORMANCE IN NIGERIA? (Journal of Global Accounting, 2025)
The study focused on evaluating the relationship between Insurance and Wealth Management Income and Advisory Service Income as non-interest income sources, and the performance of commercial banks in Nigeria. In specific terms, it determined the relationship between Insurance and Wealth Management Income, Advisory Service Income and Return on Equity of commercial banks in Nigeria.. A total of 7 licensed listed commercial banks with international capacity was sampled over a period of 12 years ranging from 2012-2023. Data were descriptively and inferentially analysed using the panel estimated generalised least square. The findings revealed that Insurance and Wealth Management Income has a negative but significant effect on Return on Equity of commercial banks in Nigeria (p-value = 0.3467). It was also discovered that the effect of Advisory Service Income on the Return on Equity of commercial banks is both negative and non-significant (p-value = 0.2700). The study therefore concluded that the negative yet non-significant relationships observed in some components of non-interest income reveal potential inefficiencies or market limitations in monetizing these streams.  It was recommended that the Heads of Insurance and Wealth Management Units should focus on improving product development and customer engagement strategies for insurance and wealth management services. Introduce tailored products that cater to diverse client needs and establish stronger partnerships with clients through financial literacy programs and personalized consultations, ensuring these services become more effective drivers of equity performance.
Keywords: Advisory Service Income; Commercial Banks; Insurance & Wealth Management Income; Return on Equity